Jewelry box inspired by Loke Hall / Aida Husna Mohamad Zaki - Mohamad Zaki, Aida Husna (2022)
Loke Chow Kit Mansion, (or simply 'Loke Hall') was constructed around 1903 - 1907, a time when Kuala Lumpur was still a growing tin mining town under the British colonial administration. The manor was believed to be designed by A.K. Through ideation and idea of development, the motif, shape, form and aesthetic line "Loke Hall" were transformed into the design for the Loke Hall.